Peran Muhammadiyah dalam Pengembangan Kewirausahaan di Indonesia - Aulia Rahmadanti; Andhini Trihapsary; Nova Damai Yanti Bancin; Masjuwita Aulia Munthe; Wismanto Wismanto; Wira Ramashar (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Muhammadiyah's role in developing entrepreneurship in Indonesia, which has made a significant contribution to community economic empowerment. Muhammadiyah, as a socio-religious organization, not only operates in the fields of education and health, but also actively encourages the development of small and medium enterprises (UKM) through various entrepreneurial initiatives. The aim of this research is to reveal the role of Muhammadiyah in developing entrepreneurship in Indonesia. This research method uses a qualitative method with a descriptive approach to analyze Muhammadiyah's efforts to create entrepreneurs who are independent, ethical and based on Islamic values. The research results show that Muhammadiyah plays a major role in increasing the capacity of young entrepreneurs through entrepreneurship education and training, with the support of institutions such as the Muhammadiyah Business Center. Muhammadiyah has also succeeded in collaborating with the government and the private sector to provide access to capital and training for business actors. With great potential in building a sustainable and ethics-based entrepreneurial ecosystem, Muhammadiyah is expected to continue to be an important actor in developing entrepreneurship in Indonesia.